HUBUNGAN LINGKUNGAN KERJA DENGAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUMAH SAKIT SWASTA BANDUNG BARAT - Yuanita Ani Susilowati; Nurul Pratiwi; Tina Shinta Parulian Siahaan (Jurnal Kesehatan, 2022)
Nursing Care Documentation is an umbrella for nurses as responsibility and accountability. However, its implementation in hospital is often contrained by limited time, knowledge and infrastructure. The purpuse of this study was to determine the relationship between the work environment and the documentation of nursing care. This study used a quantitative method with a cross-sectional design. The sample technique used total sampling with a total sample of 85 nurses who documented nursing care. Based on the results of data analysis, more than 50% of respondents said that the work environment was good. The results of observations made by researchers, 80% of nurses in inpatient rooms document nursing care properly. Bivariate analysis using the chi square test obtained a p-value of 0.000 < α, which means that there is a significant relationship between the work environment and the documentation of nursing care. conclusion, the documentation of nursing care is influenced by the quality of leadership, leadership style, programs and policies, professional development, autonomy and interdisciplinary relations which all have a p.value of 0.000 < α (0.05) which means a significant effect. Advice, maintain and continue to improve the quality of nursing care through proper and correct documentation of nursing care. Keywords : Documentation, Nursing Care, Work environment,